2016
DOI: 10.3906/yer-1605-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of natural radioactivity and assessment of radioactive dose of Western Anatolian plutons, Turkey

Abstract: IntroductionAll varieties of building materials, including various naturally occurring as well as artificial materials, have varying concentrations of Ra, Th, and K and can cause direct radiation exposure to human beings. Granite, as a market term, includes a wide variety of rock types including plutonic, volcanic, and metamorphic rocks. Granite's durability and appearance make it a popular building material in dwellings. These rocks can contain various amounts of minerals with high Ra, Th, and K concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Thick solid line: average 40 K activity measured from granite samples. Thin solid line: average 40 K activity reported for typical granitesPapadopoulos et al (2016) reported 40 K activity values ranging from 148 Bq kg −1 to 2518 Bq kg −1 with a mean value of 1097 Bq kg −1 for 70 samples of granites collected from plutons in western Anatolia (Turkey). Commercial granite rock used as building materials investigated byPavlidou et al (2006; 16 samples from Greece) andTzortzis et al (2003; 28 samples from Cyprus) gave mean 40 K activity values of 1104 Bq kg −1 and 1215 Bq kg −1 , respectively.…”
mentioning
confidence: 99%
“…Thick solid line: average 40 K activity measured from granite samples. Thin solid line: average 40 K activity reported for typical granitesPapadopoulos et al (2016) reported 40 K activity values ranging from 148 Bq kg −1 to 2518 Bq kg −1 with a mean value of 1097 Bq kg −1 for 70 samples of granites collected from plutons in western Anatolia (Turkey). Commercial granite rock used as building materials investigated byPavlidou et al (2006; 16 samples from Greece) andTzortzis et al (2003; 28 samples from Cyprus) gave mean 40 K activity values of 1104 Bq kg −1 and 1215 Bq kg −1 , respectively.…”
mentioning
confidence: 99%
“…As shown in Table-3, activity concentration of the 238 U, 232 Th and 40 K are the lowest value in Greece region [19] and Baghdad Market [28], respectively. In present study, 238 U, 232 Th and 40 K activity concentration of tobacco samples are higher than other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, 238 U, 232 Th and 40 K activity concentration of tobacco samples are higher than other studies. Because the activity concentration of natural radionuclides can be affected by the area where the tobacco is planted and the geological characteristics of the zone [28]. As a result, the activity concentrations of radionuclides may vary depending on the geological characteristics of the soil where tobacco plants are grown and the amount of fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Granites from the easternmost part of the Sudetes (Opava Mountains) gave 232 Th values ranging from 7 (weathered granite) to 54 Bq kg -1 (granite) (Dżaluk et al, 2018) . Papadopoulos et al (2016) reported 232 Th activities ranging from 0.14 to 241 Bq kg -1 with a mean value of 90 Bq kg -1 . These values significantly exceeded average 232 Th values reported here for mine samples.…”
Section: Granitesmentioning
confidence: 99%
“…40 K activity values of 1560 Bq kg -1(Dżaluk et al, 2018) Papadopoulos et al (2016). reported40 K activity values ranging from 148 Bq kg -1 to 2518 Bq kg -1 with a mean value of 1097 Bq kg -1 for 70 samples of granites collected from plutons in western Anatolia(Turkey).…”
mentioning
confidence: 99%